2021
DOI: 10.1038/s41598-021-00619-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of hematopoietic stem cells after in vitro amplification on biomimetic 3D PDMS cell culture scaffolds

Abstract: Hematopoietic stem cell (HSC) transplantation is successfully applied since the late 1950s. However, its efficacy can be impaired by insufficient numbers of donor HSCs. A promising strategy to overcome this hurdle is the use of an advanced ex vivo culture system that supports the proliferation and, at the same time, maintains the pluripotency of HSCs. Therefore, we have developed artificial 3D bone marrow-like scaffolds made of polydimethylsiloxane (PDMS) that model the natural HSC niche in vitro. These 3D PDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
0
10
0
1
Order By: Relevance
“…3D hydrogel co-cultures are frequently used in tissue engineering for reproducing stem cell niche environments, such as satellite cell niche in muscle cell regeneration [ 18 , 26 , 35 ]. Hydrogels are also a suitable biomaterial for in vitro studies, as they can be easily degraded, and cells can be harvested and used for further experiments [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 34 , 36 , 37 , 38 ]. Moreover, the three-dimensionality of hydrogels creates a hypoxic gradient, naturally present in the marrow, thus better mimicking the BM niche [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…3D hydrogel co-cultures are frequently used in tissue engineering for reproducing stem cell niche environments, such as satellite cell niche in muscle cell regeneration [ 18 , 26 , 35 ]. Hydrogels are also a suitable biomaterial for in vitro studies, as they can be easily degraded, and cells can be harvested and used for further experiments [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 34 , 36 , 37 , 38 ]. Moreover, the three-dimensionality of hydrogels creates a hypoxic gradient, naturally present in the marrow, thus better mimicking the BM niche [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights the need for further studies on MSC biology considering the in vitro and in vivo contexts. In line with this, a recent research work developed an ex vivo culture system based on 3D bone marrow-like scaffolds to characterize hematopoietic stem cells at the molecular level [ 57 ]. In particular, they found that cells grown in polydimethylsiloxane scaffolds activated the forkhead box O (FOXO), sterol regulatory element-binding proteins (SREBP) and hypoxia inducible factor 1-alpha (HIF-1α) pathways, which potentiated fatty acids/cholesterol metabolism and reduced mitochondrial respiration, creating an optimized environment for cell expansion.…”
Section: Changes Induced In Mscs During In Vitro Expansionmentioning
confidence: 99%
“…A recent study discovered that a 3D culture in a zwitterionic hydrogel can expand phenotypically primitive CD34+ cord blood and BM-derived HSPCs, which achieved substantial expansion of LT-HSCs frequency. The expansion of HSCs was reached via the inhibition of HSPC differentiation and increased self-renewal caused by the 3D zwitterionic hydrogel culture because of an inhibition of excessive ROS production by suppressing O-related metabolism [ 53 ]. However, the culture condition, the zwitterionic characteristics of the hydrogel and the 3D format are both vital for the expansion [ 54 ].…”
Section: Ex Vivo Expansion Of Hscsmentioning
confidence: 99%